RETRACTED: SUMBANGAN ILMU ETNOBOTANI DALAM MEMFASILITASI HUBUNGAN MANUSIA DENGAN TUMBUHAN DAN LINGKUNGANNYA [ CONTRIBUTIONS IN SCIENCE ETHNOBOTANY FACILITATE HUMAN RELATIONS WITH PLANTS AND ENVIRONMENT ] - Insan Wijaya; Oktarina Oktarina (Universitas Muhammadiyah Jember, 2014)
This article has been retracted at the request of the Editor-in-Chief and Publisher. Please see the withdrawal policy.Reason: This article identical to the previously published article:“Sumbangan Ilmu Etnobotani dalam Memfasilitasi Hubungan Manusia dengan Tumbuhan dan Lingkungannya”, Jurnal Biologi Indonesia, Vol 7, No 2 (2011) 375-391 authored by Eko Baroto Walujo.